2019
DOI: 10.1101/736108
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Collective interactions augment influenza A virus replication in a host-dependent manner

Abstract: 22implicated the PA gene segment as a major driver of this phenotype and quantification of viral 33RNA synthesis indicated that both replication and transcription were affected. These findings 34 indicate that multiple distinct mechanisms underlie IAV reliance on multiple infection and 35 underscore the importance of virus-virus interactions in IAV infection, evolution and emergence. 36Importantly, multiple infection with identical viral genomes can also alter infection 58 outcomes. Such cooperation was docume… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(37 citation statements)
references
References 86 publications
2
35
0
Order By: Relevance
“…A model that allows for the onset times of viral production to depend on cellular MOI may therefore better capture the relationship between viral output and cellular MOI at this early time point. Our overall results are consistent with previous reports of earlier and higher rates of replication under high experimental MOI conditions [ 19 , 20 ].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…A model that allows for the onset times of viral production to depend on cellular MOI may therefore better capture the relationship between viral output and cellular MOI at this early time point. Our overall results are consistent with previous reports of earlier and higher rates of replication under high experimental MOI conditions [ 19 , 20 ].…”
Section: Resultssupporting
confidence: 93%
“…Specifically, they observed an inverse relationship between the susceptibility of a given cell line to VSV infection and the extent to which cellular co-infection enhanced viral output. Similarly, Phipps et al observed that cellular co-infection could enhance influenza virus replication when the virus strain used was poorly adapted to the cell line used [ 20 ]. Along with these studies, our results illustrate the importance of considering variation between cell types.…”
Section: Discussionmentioning
confidence: 99%
“…A model that allows for the onset times of viral production to depend on cellular MOI may therefore better capture the relationship between viral output and cellular MOI at this early time point. Our overall results are consistent with previous reports of earlier and higher rates of replication under high experimental MOI conditions (19,20). For A549 cells, we considered the same set of time-dependent virus production rate models.…”
Section: Cellular Co-infection Increases the Rate Of Virus Productionsupporting
confidence: 89%
“…Viral output from cells can be affected by host cell characteristics such as size, cell type, and cell cycle stage (Brooke et al, 2013; Schulte and Andino, 2014; Heldt et al, 2015; Golumbeanu et al, 2018; Leviyang and Griva, 2018; Russell et al, 2018; Xin et al, 2018; Phipps et al, 2019; Vera et al, 2019). To consider the effect of heterogeneity in virus output on deleterious mutation accumulation, we extend our base model described above by adapting an approach used by Lloyd-Smith et al (2005) to describe population-level viral transmission heterogeneity (superspreading dynamics).…”
Section: Modelmentioning
confidence: 99%
“…Virus output from cells can also be affected by cellular multiplicity of infection, with higher cellular MOI having the potential to increase viral yield (Phipps et al, 2019; Martin et al, 2020). To consider the effect that this source of cellular heterogeneity in virus output may have on deleterious mutation accumulation, we extended the base model to allow cellular multiplicity of infection to impact cellular output.…”
Section: Modelmentioning
confidence: 99%